BURHANUDDIN AL-MARGHINANI ON THE TYPES AND PROCEDURES OF TAXES LEVIED ON THE POPULATION RESIDING IN CONQUERED TERRITORIES - Toshqulov Jo‘raboy (Modern American Journals, 2025)
This article examines Burhanuddin al-Marghinani's perspectives on the taxation system in the Islamic state as presented in his treatise “al-Hidaya.” It focuses on the types of taxes such as ushr, kharaj, and jizya, procedures for collection, identification of taxpayers and exemptions, as well as legal interpretations concerning the use and distribution of collected taxes in accordance with Sharia principles.
Keywords: Marghinani, al-Hidaya, ushr, kharaj, jizya, Islamic law, taxation, dhimmi, bayt al-mal, conquest, dar al-Islam